THE EFFECT OF GREEN HUMAN RESOURCE MANAGEMENT (GHRM) PRACTICES ON THE COMPETITIVENESS OF HIGHER EDUCATION MEDIATED BY KNOWLEDGE MANAGEMENT - Sukardi, Sukardi; Djumarno, Djumarno; Herminingsih, Anik; Kasmir, Kasmir; Widayati, C. Catur; Zairil, Zairil (Universitas Brawijaya, Indonesia, 2023)
In the global era, creating competitiveness is one of the key aspects of survival. This study aims to explain competitiveness in knowledge management-mediated green human resource management practices in Jakarta's private universities. This research is critical because green practices on campus are becoming essential due to the need for sustainable development and climate change mitigation. Furthermore, educational institutions should educate global citizens about sustainable development and provide relevant information concerning environmentally friendly practices. In this research, a total sample of 356 lecturers from 10 private tertiary institutions in Jakarta with B accreditation and more than 5,000 students. Purposive sampling was used in the sampling method to collect data, which was then analyzed using SEM-PLS. According to the study results, green human resource management has a direct and positive effect on competitiveness, while green human resource management has a direct positive impact on knowledge management. It can also be stated that knowledge management measurements' findings on competitiveness have a positive effect. Further research demonstrates a positive secondary impact of green human resource management through knowledge management on competitiveness. The results of this study may have negative effects on the campus's reputation as a green educational facility.